The Importance of Character Education Based on Sundanese Culture in Guidance and Counseling: Forming Individuals with Superior Character - Gustianti, Risma; Abdillah, Muhamad Ilyas; Ilham, Ecep; Zahira, Tiara Nuri; Irmayanti, Rima (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to find out how the process and existence of character education based on Sundanese culture in guidance and counseling forms individuals with superior character, which are implemented at SMP PGRI Cibeureum, both in terms of application background, the values of Sundanese local wisdom are developed to find out how important education is. character based on Sundanese culture in counseling guidance to form individuals with superior character is a kind of field study that takes a qualitative approach. Creswell (1998) A qualitative approach is defined as a process of study and understanding based on a methodology that explores social phenomena and human concerns. In this strategy, the researcher creates complex images, analyzes language, creates extensive reports from the perspective of respondents, and conducts investigations on natural scenarios. Character education is carried out at SMP PGRI Cibeureum through methodical habituation exercises Character education is used by incorporating Sundanese cultural values